Artificial weathering and accelerated heat ageing studies on low-density polyethylene (LDPE) produced via autoclave and tubular process technologies - A. S. Luyt; S. A. Gasmi; S. S. Malik; R. M. Aljindi; M. Ouederni; S. N. Vouyiouka; A. D. Porfyris; R. Pfaendner; C. D. Papaspyrides (eXPRESS Polymer Letters, 2021)
Accelerated (artificial) weathering and thermal aging tests were performed to investigate the effectiveness of different formulations in reducing the UV/heat degradation extent for two low-density polyethylene types (LDPE-A, LDPE-T). The two LDPEs differ in the type and extent of branching due to the applied polymerization process, with LDPE-A being produced in an autoclave and LDPE-T in a tubular reactor. Oligomeric or high molecular weight hindered amine light stabilizer (HALS), and two UV absorbers of benzophenone or hydroxyphenyl-triazine types were equally introduced to both the LDPE grades at a total content of 0.2 wt%. The surface morphology, as well as thermal and mechanical properties, were examined during aging showing a significant degradation extent for the neat samples. In particular, a mechanism of chain scission/branching that resulted in crosslinking was assumed for the neat polyethylenes, after combining the decrease of molecular weight observed in the GPC analysis with the increase in Young’s modulus after UV exposure. LDPE-T presented higher photo-oxidation rates due to its comb-like branched structure and its higher possibility of intermolecular reactions between adjacent chains. Little or no degradation was observed for the stabilized grades, confirming the effectiveness of the selected UV/heat systems in improving the weathering resistance of the two LDPE grades and enhancing their useful lifetime.